2008
DOI: 10.1007/s11695-008-9721-6
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Course of Patients Submitted to Bariatric Surgery

Abstract: RYGBP was effective for weight loss and for the reduction of obesity rates and risk factors for comorbidities. The diet of these patients, who frequently present inadequate intake of macronutrients and micronutrients, should receive special attention. Patient follow-up and assessment at short intervals are necessary for an early correction of nutritional deficiencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
1
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(102 citation statements)
references
References 21 publications
4
86
1
11
Order By: Relevance
“…Patients should be repeatedly educated about staged meal progression dependent on the time elapsed after surgery and based on the type of surgical procedure they underwent (EL A, B, C, D [177][178][179][180][181][182][183][184][185] ). Patients should also be informed that an excessive number and size of meals will probably result in lower weight loss.…”
Section: Follow-upmentioning
confidence: 99%
“…Patients should be repeatedly educated about staged meal progression dependent on the time elapsed after surgery and based on the type of surgical procedure they underwent (EL A, B, C, D [177][178][179][180][181][182][183][184][185] ). Patients should also be informed that an excessive number and size of meals will probably result in lower weight loss.…”
Section: Follow-upmentioning
confidence: 99%
“…However, changes in the nutritional quality of food intake that occur in the preoperative period must not occur during the postoperative period, as this will lead to health problems. We also analyzed fiber intake in post-surgical patients and found that fiber intake up to 12 months after surgery was less than the recommended intake [19]. This finding reflects the need for continuous nutritional education on an outpatient basis, encouraging the consumption of fruits, vegetables, whole grains, and high-fiber foods.…”
Section: Discussionmentioning
confidence: 92%
“…Some studies have indicated that protein intake in the first year after surgery may be much lower than recommended, often closer to 0.5 gm/kg. [46] Certainly, any preexisting hypoalbuminemia could be worsened if adequate protein intake is not achieved during the periods of highest caloric restriction. The reported prevalence of hypoalbuminemia in the literature ranges from 3-11%.…”
Section: Late Complications Nutritional Deficienciesmentioning
confidence: 99%
“…[46] Menstruating and pregnant females are at the greatest risk. Anemia can also be exacerbated by chronic inflammation secondary to obesity.…”
Section: Late Complications Nutritional Deficienciesmentioning
confidence: 99%